Reconfiguring modernity : concepts of nature in Japanese political ideology - Thomas, Julia Adeney, (University of California Press)
1. Introduction: The Trouble with Nature Objections Justifications Outline of Nature's Political History in Japan 2. The Topographical Imagination of Tokugawa Politics Mental Maps China as Imperial Center Japan's Imperial Center Rural Centers Centers of Learning Divorce Proceedings: Space versus Time 3. Early Meiji's Contentious Natures Natural Forms of Contention: Laws and Bodies The Historiography of Meiji Ideologies Nature's Indeterminate Determinism 4. Kato Hiroyuki: Turning Nature into Time Kato Hiroyuki and Tenko Shinsei tai'i and Kokutai shinron Jinken shinsetsu The Reaction to Jinken shinsetsu 5. Baba Tatsui: Natural Laws and Willful Natures The Equilibrium of Forces in Nature and History The Death Wishes of Baba Tatsui and Herbert Spencer Tenpu jinkenron: The Reply to Kato Catalyzing Nature: The Role of Will in Baba's Social Evolution 6. Ueki Emori: Singing the Body Electric The Basic Body of Tenpu jinkenben The Political Problems of Ueki's Bodies A Dance of Loneliness 7. The Acculturation of Japanese Nature Social Evolution's Victory Social Evolution's Defeat: The Political Inadequacy of a Progressive Cosmopolis Nature as Japanese Culture: Bringing the Outside In The Last Vestiges of Social Darwinism 8. Ultranational Nature: Dead Time and Dead Space Shinto's National Nature Economizing Nature Educating the National Family World-Historical Nature 9. Conclusion: Natural Freedom